2021
DOI: 10.1021/acsami.0c18474
|View full text |Cite
|
Sign up to set email alerts
|

Smart Textiles with Self-Disinfection and Photothermochromic Effects

Abstract: Self-disinfecting textile materials employing combined photodynamic/photothermal effects enable the prevention of microbial infections, a property that has great potential in healthcare applications. However, smart textiles with stimulus responses to ambient temperature are marvelous materials for enhancing their photothermal applications with additional functions. It is still challenging to realize vivid and contrasting color changes as temperature indicators. Herein, through the in situ growth of PCN-224 met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 52 publications
(64 reference statements)
0
34
0
1
Order By: Relevance
“…In the context of this review, the term drug implies the photosensitizer with its various components including composites (MOF or COF physiosorbed to a noninnocent inorganic or organic nanomaterial). The use of porphyrin-based 2D and 3D MOFs and COFs as photosensitizers, catalysts, or simply a platform containing other residues for the eradication of bacteria has indeed experienced an impressive boom in the past few years. , Applications in plant management have also been reported, which represents a new topic of research for MOFs . Additionally, some MOFs were used as sensors of drug-resistant bacteria using PCN-224 (the structure is shown in Figure ).…”
Section: Mof and Cof Designs And Related Propertiesmentioning
confidence: 99%
“…In the context of this review, the term drug implies the photosensitizer with its various components including composites (MOF or COF physiosorbed to a noninnocent inorganic or organic nanomaterial). The use of porphyrin-based 2D and 3D MOFs and COFs as photosensitizers, catalysts, or simply a platform containing other residues for the eradication of bacteria has indeed experienced an impressive boom in the past few years. , Applications in plant management have also been reported, which represents a new topic of research for MOFs . Additionally, some MOFs were used as sensors of drug-resistant bacteria using PCN-224 (the structure is shown in Figure ).…”
Section: Mof and Cof Designs And Related Propertiesmentioning
confidence: 99%
“…We further investigated the antibacterial mechanism of our strategy in vitro. As large bodies of literature suggested that generation of intracellular ROS was a key mechanism to effectively kill the invading bacteria, [ 9,22,41,42 ] we specifically characterized the change of intracellular ROS level of bacteria in response to designated treatments. Green fluorescent signal was clearly observed in MAO+ZI group after irradiation ( Figure A), while no fluorescence signals were found in the control groups, suggesting a dramatically‐increased intracellular ROS level in MAO+ZI after NIR exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Nie and co-workers demonstrated the synthesis of MXene and MOF hybrids by a facile mixing approach which was then employed for the fabrication of smart textile. 95 After the synthesis of PCN-224 MOF-modified cotton fabric (CF), the formation of hybrid was achieved by electrochemically spraying Ti 3 C 2 T x MXene aqueous solution over it. Further, thermochromic dye was introduced into the CF@PCN hybrid toward exploitation of photothermochromic effects.…”
Section: Facile Mixing Methodsmentioning
confidence: 99%
“…Very recently, Nie and co-workers successfully achieved the synthesis of MXene and MOF-based smart textiles having photothermochromic effect and self-disinfection property. 95 PCN-224 MOF was grown on cotton fabric (CF) to get CF@ PCN, which was then electro-sprayed with an aqueous solution Ti 3 C 2 to obtain CF@PCN x (where x = MXene wt cm −3 ). Finally, the smart textile (S-CF@PCN x ) was obtained by coating its surface with a thermochromic dye.…”
Section: Applications Of Mxene@mof Materialsmentioning
confidence: 99%